Disposable Bodies, Disabled Minds, and Christian Hope: Resurrection in Light of Transhumanism and Intellectual Disability - Sloane, Andrew (Zygon, 2023)
This piece brings into critical conversation Christian resurrection hope, virtual versions of transhumanism, and intellectual disability and demonstrates that Christian resurrection provides a more cogent hope for people with severe intellectual disabilities than transhumanism. I argue that transhumanist virtual futures are theologically problematic, as bodily resurrection is neither required nor desirable. It is particularly problematic for people with severe intellectual disabilities given the way they would be excluded from these futures. Disability theology also raises issues with the traditional notions of “healing” in the resurrection and the implications for the value and identity of persons with intellectual disabilities. Starting with these problems, I explore the nature of Christian hope, noting the inadequacies of a virtual transhumanist future with respect to both resurrection faith and intellectual disability, and address how resurrection hope can account for issues raised in disability theology, and so properly include people with intellectual disabilities.